Etnomatematika: Eksplorasi Rumah Adat Taslulu Nabesleu Koafnolo Pada Konsep Geometri - Jefrianus Kehi, Yohanes; mariano (Jurnal Dimensi Matematika, 2023)
Culture is a way of life that is developed and shared by a group of people and inherited from generation to generation. Culture is formed from various complex elements, including belief systems, norms, values, customs, and languange. Ethnomathematics also plays an important role in exploring noble values in the culture of the community. This study has the aim of the researcher being to describe and document the results of the ethnomathematical exploration of the geometric concept of the Taslulu Nabesleu Koafnolo traditional house building. The type of research used in this research is qualitative research. Data collection techniques used are observation, interviews and documentation. There are several geometric concepts in the design of the Taslulu Nabesleu Koafnolo traditional house, namely the concept of flat wake, the concept of building a flat side space, the concept of the relationship between lines, the concept of angles, and geometric transformations. The results of the study are expected to help teachers explain mathematical concepts as well as introduce the culture of the Taslulu Nabesleu Koafnolo Traditional House.